Photodetectors Based on Micro-nano Structure Material - Yu, Yu; Wang, Wuyue; Li, Weihua; Wang, Gong; Wang, Yulei; Lu, Zhiwei; Li, Sensen; Zhao, Wanli; Li, Yuhai; Liu, Tongyu; Yan, Xiusheng (Frontiers in Chemistry, 2022)
Photodetectors converting optical signals into electrical signals have been widely utilized and have received more and more attention in scientific research and industrial fields including optical interconnection, optical communication, and environmental monitoring. Herein, we summarize the latest development of photodetectors with different micro-nano structures and different materials and the performance indicators of photodetectors. Several photodetectors, such as flexible, ultraviolet (UV), two-dimensional (2D) microscale, and dual-band photodetectors, are listed in this minireview. Meanwhile, the current bottleneck and future development prospects of the photodetector are discussed.